2008
DOI: 10.1080/17453670710015526
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity‐related quality of life in anterior cruciate ligament insufficiency: A cross‐sectional study involving 282 candidates for arthroscopic reconstruction

Abstract: Comorbidity-related HRQoL in ACL-insufficient candidates for arthroscopic reconstruction showed statistically significant differences from the norm. Comorbid illness acting as confounder should thus be controlled for when reporting SF-36 profiles, in order to avoid selection bias. Our findings may also be used as benchmark data for researchers investigating SF-36 profiles in ACLI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…22,24 Finally, we evaluated the association between common comorbid conditions and the risk of revision ACL reconstruction after primary ACL reconstruction. The increased risk of revision ACL reconstruction among patients with diseases of the back or back pain is in accordance with the results of Calvisi et al, 20 who found an association between comorbidity and Short Form 36 profiles in ACL-insufficient patients. It seems obvious that there is an association between comorbidity and Short Form 36, which is a questionnaire evaluating quality of life.…”
Section: Comorbidity Of 13443 Acl-injured Patientssupporting
confidence: 84%
See 2 more Smart Citations
“…22,24 Finally, we evaluated the association between common comorbid conditions and the risk of revision ACL reconstruction after primary ACL reconstruction. The increased risk of revision ACL reconstruction among patients with diseases of the back or back pain is in accordance with the results of Calvisi et al, 20 who found an association between comorbidity and Short Form 36 profiles in ACL-insufficient patients. It seems obvious that there is an association between comorbidity and Short Form 36, which is a questionnaire evaluating quality of life.…”
Section: Comorbidity Of 13443 Acl-injured Patientssupporting
confidence: 84%
“…Although a large variety of diseases were present in the ACL-reconstructed group, the high prevalence of a CCI equal to 0 did indicate that the severity of their illness was low. Calvisi et al 20 conducted a cross-sectional study of 282 ACL-insufficient patients to assess comorbidity-adjusted health-related quality of life in ACL-insufficient patients and to determine if these patients differ from the Italian norm. The comorbid conditions were self-reported, which increases the risk of information bias.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been advocated that assessment of HRQoL should be incorporated for outcome assessment in patients with ACL insufficiency [7]. However, a recent report demonstrated that comorbidity should be controlled when assessing HRQoL in candidates for ACL reconstruction because it acts as a confounder [8]. …”
Section: Introductionmentioning
confidence: 99%